ANTIVIRAL THERAPY FOR HERPES SIMPLEX VIRUS ENCEPHALITIS: SYSTEMATIC REVIEW - Annurul Maulidia, Agnes; Yuni Kurniawati, Media (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Without regard to treatment, herpes simplex encephalitis is detrimental. Neonatal encephalitis caused by HSV-2 affects the brain more extensively, resulting in more neurologic complications. Viral variables and host immune responses determine virulence and invasiveness in adults. In order to maintain latency, it is necessary to inhibit viral lytic-phase genes and modify innate and adaptive immune responses to thwart host cellular defenses.The aim: This article explore effectiveness and safety antiviral therapy for herpes simplex virus encephalitis.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 67 articles, whereas the results of our search on SagePub brought up 53 articles. The results of the search conducted for the last year of 2010 yielded a total 11 articles for PubMed and 3 articles for SagePub. In the end, we compiled a total of 8 papers, 7 of which came from PubMed and one of which came from SagePub. We included two research that met the criteria.Conclusion: The standard treatment of HSV-1 encephalitis is IV acyclovir, as PO acyclovir and valacyclovir require multiple doses per day.